Strategi Pengelolaan Peternakan Ayam Ras Pedaging di Kecamatan Pujud - Roflimas Roflimas; Eddiwan Eddiwan; Zulkarnain Zulkarnain (Pelantar Press, 2024)
Livestock development is an important aspect of agricultural development, especially during the economic and monetary crisis. The role of the livestock sub-sector in agricultural development is quite significant, one of which is the poultry industry. Apart from that, an increase in the broiler chicken population will certainly have several environmental and social impacts felt by breeders and other people who are near the farm. The aim of this research is to find out appropriate strategies to be applied in Pujud District, Rokan Hilir Regency in efforts to manage broiler chicken businesses. The survey was conducted using interview techniques, questionnaires and literature study. Interview and distribute questionnaires to breeders and communities around broiler cages in Pujud District. The analysis used is SWOT analysis. The results of research on the best strategy for managing the broiler chicken business in Pujud District, Rokan Hilir Regency is to utilize the availability of raw materials, the availability of sufficient capital to meet the high demand for chicken meat, increasing good cooperation with sapronak suppliers and collectors/agents in order to balance needs. restaurants that grow rapidly and reduce production costs by utilizing experienced employees to produce low-cost products and maintain social relations with the community and can become a source of additional income for the community.